STRATEGI PERAWATAN KAMBING PERANAKAN ETAWA (PE) JANTAN UNTUK TUJUAN KONTES PETERNAKAN DI NRJ FARM BOYOLALI: STRATEGY FOR CARING FOR MALE ETAWA CROSSBREED GOATS FOR LIVESTOCK CONTEST PURPOSES AT NRJ FARM BOYOLALI - Nefvian, Moh Edo; Purwadi, Purwadi; Prasetyo, Aris Budi (Tropical Animal Science, 2025)
This study aims to determine the optimal care strategy for Etawa crossbred goats (PE) for contest purposes at NRJ farm. The materials used in this study were questionnaires and respondents, the equipment used included motor transportation, Android phones and stationery. The methods used were surveys, observations, and direct practice for three weeks, then the results were presented descriptively. The method of determining respondents was carried out by purposive sampling or intentionally meeting the established criteria. Data collection used a questionnaire containing questions about male PE goat care techniques for contest purposes. And using parameters of seed quality, feed/supplement quality, intensive care, special treatment/strategy aspects and housing. The data obtained were collected and then concluded using a qualitative approach. Obstacles will be analyzed using SWOT. The results of this study include intensive care techniques and special care for male PE goats for livestock contest purposes applied at NRJ Farm Boyolali. The results of the study can improve understanding of the care needs of PE contest goats and develop better educational resources for other contest goat breeders. The conclusion of the results of this study is that the optimal intensive care technique and care strategy for male PE goats at NRJ farm Boyolali will improve quality and maintain achievements in livestock contests.